Muslim Women Empowerment In Miss Hijab Indonesia Instagram Content: Analysis Of Social Media Content On The @Officialmisshijabindonesia Instagram Account - Dio Nurkholis; Augustin Mustica Chairil (Lavish Opulent Education, 2026)
The development of social media as a space for the formation of Muslim women’s identity, particularly in religious-based beauty pageants such as Miss Hijab Indonesia, integrates aspects of beauty, intellect, and spirituality in digital representation. The problem addressed in this study is how Islamic femininity is portrayed in the Instagram content of @officialmisshijabindonesia. This study aims to understand the construction of Muslimah Empowerment in social media through content analysis. The method used is a descriptive qualitative approach with content analysis of posts within a specified period, employing a constructivist paradigm and categorization based on the concept of Muslimah Empowerment according to KH Husein Muhammad, which is divided into four aspects: tauhid and gender equality, modern Muslimah jihad, emancipatory fiqh, and empowered Muslimah. The results of this study show a consistent pattern of representation in portraying Muslim women, including winners and finalists of Miss Hijab Indonesia, as active and empowered figures through captions, visuals, and narratives containing educational, inspirational, and da’wah values. The content of Miss Hijab Indonesia may include more than one category of empowerment that are interconnected. The conclusion of this study is that the Instagram account @officialmisshijabindonesia not only represents the standard of Muslim women’s beauty but also constructs Muslimah Empowerment that consistently integrates Islamic values with modern digital identity.